Impossible Puzzle Films: A Cognitive Approach to Contemporary Complex Cinema - Kiss, Miklós and Willemsen, Steven (Edinburgh University Press, 2022)
Frontmatter -- Contents -- Acknowledgements -- Introduction -- I.1 In this book -- Chapter 1 Contemporary Complex Cinema -- 1.1 Complex conditions: the resurgence of narrative complexity -- 1.2 Complex cinema as brain-candy for the empowered viewer -- 1.3 Narrative taxonomies: simple, complex, puzzle plots -- Chapter 2 Cognitive Approach to Contemporary Complex Cinema -- 2.1 Why an (embodied-)cognitive approach? -- 2.2 Various forms of complexity and their effects on sense-making -- 2.3 A cognitive approach to classifying complexity -- Chapter 3 Narrative Complexity and Dissonant Cognitions -- 3.1 The concept of cognitive dissonance -- 3.2 Cognitions in dissonance: from social psychology to narrative engagement -- 3.3 Types of dissonance in narrative comprehension -- 3.4 Cognitive access to impossible storyworlds: immersed and reflected operations -- 3.5 'Impossibilities' and embodied cognition -- Chapter 4 Taming Dissonance: Cognitive Operations and Interpretive Strategies -- 4.1 Cognitive dissonance versus narrative coherence -- 4.2 Reducing dissonance: interpretation and naturalisation -- 4.3 Coping with dissonance: frame-switches and poetic and aesthetic readings -- 4.4 Frame-switching as hermeneutic play in impossible puzzle films -- Chapter 5 Impossible Puzzle Films: Between Art Cinema and (Post-)Classical Narration -- 5.2 Impossible puzzle films and (post-)classical narration -- Chapter 6 Wallowing in Dissonance: The Attractiveness of Impossible Puzzles -- 6.1 Hermeneutic play and interpretive multiplicity -- 6.2 Orientation, navigation, mapping -- 6.3 Game logic and the fascination in failure -- 6.4 Effort justification -- 6.5 Diegetisation of decoupling -- 6.6 Fascination in infinity -- 6.7 Destabilised ontological certainty -- 6.8. Eudaimonic motivations and intrinsic needs -- References -- Filmography -- Index
https://katalog.adlr.link/Record/0-1795214406